2017
DOI: 10.3892/etm.2017.4475
|View full text |Cite
|
Sign up to set email alerts
|

Metformin ameliorates diabetic nephropathy in a rat model of low-dose streptozotocin-induced diabetes

Abstract: Abstract. The present study aimed to explore the renoprotective effect of metformin on diabetic nephropathy in type 2 diabetic rats. A rat model of type 2 diabetic nephropathy (T2DN) was successfully induced via a high-fat diet combined with a single low-dose of streptozotocin. Metformin was administered intragastrically for 13 weeks, and fasting blood glucose (FBG), total cholesterol (TC), triglycerides (TG), HDL-c, LDL-c, urinary and serum creatinine levels were subsequently examined at the end of administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
74
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 51 publications
12
74
1
2
Order By: Relevance
“…Results of treated group of our study regarding reduction in creatinine and urea levels are in conformity with the study conducted by Zhang et al [47]. …”
Section: Methodssupporting
confidence: 92%
“…Results of treated group of our study regarding reduction in creatinine and urea levels are in conformity with the study conducted by Zhang et al [47]. …”
Section: Methodssupporting
confidence: 92%
“…Serum was collected to analyze LPS, blood glucose, TC, TG, high‐density lipoprotein cholesterol (HDL‐c), LDL‐c, pancreas tissue for gene expression of phosphoinosmde‐3‐kinase (PI3K), protein kinase B (Akt), IL‐2, IL‐6, TNF‐α, TGF‐β, and contents of colon for gut microbiota. Blood biochemical parameters were determined by the Health Science Center of Peking University (Pecking, China) as previously described …”
Section: Methodsmentioning
confidence: 99%
“…However, the present study measured GFR directly by clearance of inulin and estimated filtration barrier integrity from urinary excretion of albumin in order to avoid the commonly acknowledged problems associated with tubular handling of creatinine in rodents . Importantly, previous studies have reported beneficial effects of metformin on DKD when treating for 8 to 13 weeks after the onset of diabetes . In the present study, we investigated the effect of metformin on intrarenal oxygen availability already after 4 weeks of diabetes duration, since we hypothesize that early changes in kidney oxygen metabolism is a crucial component for the onset and progression of DKD.…”
Section: Discussionmentioning
confidence: 99%
“…The renal medulla is especially sensitive to hypoxia due to low blood perfusion and high basal levels of QO 2. The renoprotective effects of metformin have been reported in several animal studies, including unilateral ureteral obstruction and gentamicin‐induced nephropathy as well as in DKD . Metformin is a drug with pleotropic effects and has been suggested to protect against DKD through AMP‐activated protein kinase/mammalian target of rapamycin modulation, attenuation of hypoxia‐inducible factor 1‐alpha accumulation, and through modulation of oxidative stress‐related gene expression …”
Section: Introductionmentioning
confidence: 99%